ANALISIS BARGAINING POWER INDONESIA DAN PT FREEPORT INDONESIA DALAM NEGOSIASI PENGALIHAN KONTRAK KARYA MENJADI IZIN USAHA PERTAMBANGAN KHUSUS TAHUN 2017 – 2018 - Raharja, I Ketut; Widya Nugraha, A.A. Bagus Surya; Prameswari, Anak Agung Ayu Intan (Program Studi Hubungan Internasional FISIP Universitas Udayana, 2020)
ABSTRACT This research attempt to explain bargaining power of Indonesia and PT Freeport Indonesia in negotiating the transfer of Kontrak Karya to Izin Usaha Pertambangan Khusus from 2017 to 2018, using qualitative methods and the concept of Bargaining power as a framework. Indonesia is the Host Country of PT Freeport Indonesia. PT Freeport Indonesia also a subsidiary of Freeport McMoran. In 2017, Indonesia and PT Freeport Indonesia negotiated the transfer of Kontrak Karya to Izin Usaha Pertambangan Khusus which both of the actors used their power for the negotiations. In this research, analyze the power that owned by each actor will determine the outcome or the result of the negotiations. In addition, the negotiations in this research were carried out by two different actors, Indonesia as a State, and PT Freeport Indonesia as a Multinational Corporations which has different cost and benefit calculations. Keywords: Indonesia, Kontrak Karya, Izin Usaha Pertambangan Khusus, Bargaining power